Novel thymoquinone loaded chitosan-lecithin micelles for effective wound healing: Development, characterization, and preclinical evaluation. (15th February 2020) - Negi, Poonam; Sharma, Gulshan; Verma, Chetna; Garg, Prakrati; Rathore, Charul; Kulshrestha, Saurabh; Lal, Uma Ranjan; Gupta, Bhuvanesh; Pathania, Deepak
Graphical abstract: Highlights: Lecithin conjugated copolymer of chitosan was used to synthesize polymeric micelles. The copolymer possess low critical micelle concentration suggesting it's self-assembly character. The optimized polymeric micelle exhibited the requisite small particle size, narrow size distribution, and high entrapment efficiency. Hydrogel loaded with TQ-polymeric micelle exhibited superior wound healing efficacy. Abstract: While the wound healing activity of thymoquinone (TQ) is well known, its clinical effectiveness remains limited due to the inherently low aqueous solubility, resulting in suboptimal TQ exposure in the wound sites. To address these problems, TQ loaded chitosan-lecithin micelles for wound healing were prepared and its efficacy was determined in vivo in the excision wound model. Firstly, the co-block polymer of chitosan and soya lecithin was synthesized which has low critical micelle concentration (CMC). Its employment in the development of TQ loaded polymeric micelles by Self-assembly method resulted in the stable polymeric micelle composition having requisite small particle size (<100 nm), narrow size distribution (close to zero) and high entrapment efficiency (98.77 %) of TQ. The designed nano-carriers not only substantially entrapped the drug but also controlled the release rate of TQ. The TQ-polymeric micelle hydrogel exhibited superior wound healing efficacy to the native TQ and Silver Sulphadiazine.